Experimental results on pion production compared with predictions of the Isobar model - Alles-Borreli, V.; Bergia, S.; Perez Ferreira, Emma; Waloschek, Pedro (Societa italiana di fisica, 1959)
Fil: Allen-Borreli, V. Instituto Nazionale de Física Nucleare; Italia